2020
DOI: 10.3906/sag-2005-117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sacrospinous ligament fixation during vaginal hysterectomy on postoperative de novo stress incontinence occurrence: a prospective study with 2-year follow-up

Abstract: Background/aim To investigate the risk of de novo stress urinary incontinence (SUI) occurrence in women who were treated for pelvic organ prolapse (POP) with sacrospinous ligament fixation (SSLF) in addition to vaginal hysterectomy (VAH) and antero-posterior colporrhaphy (CAP) over a 24-month follow-up period. Materials and methods A prospective randomized study was designed. Women without occult or obvious SUI were randomized into either one of the study groups: Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Surgical treatment of POP may affect the mobility of the vesicourethral junction, but it might also unmask previously occult SUI. Baser et al investigated the risk of de novo SUI in women treated for POP with SSLF, with simultaneous vaginal hysterectomy and anterior-posterior colporrhaphy (n = 73, 24 months follow-up), and confirmed that SSLF did not increase the rate of de novo SUI [48]. Biler et al [15] reported two de novo urgency and one de novo SUI cases after LP, without statistical significance.…”
Section: Discussionmentioning
confidence: 97%
“…Surgical treatment of POP may affect the mobility of the vesicourethral junction, but it might also unmask previously occult SUI. Baser et al investigated the risk of de novo SUI in women treated for POP with SSLF, with simultaneous vaginal hysterectomy and anterior-posterior colporrhaphy (n = 73, 24 months follow-up), and confirmed that SSLF did not increase the rate of de novo SUI [48]. Biler et al [15] reported two de novo urgency and one de novo SUI cases after LP, without statistical significance.…”
Section: Discussionmentioning
confidence: 97%
“…The probable reason for SUI development is posterior and apical displacement of the vaginal axis; unilateral stretch of the vaginal apex could further contribute to ureterovesical angle impairment. However, Başer et al 17 observed no significant effect on incontinence rates, although the anatomical position of the urethrovesical angle was changed with the SSLF procedure.…”
Section: Discussionmentioning
confidence: 98%